Effects of a whole-body electrostimulation warm-up protocol in young semi-professional football players - Perez de Arrilucea Le Floc´h, U. A.; Naranjo Delgado, S.; Burgos-Postigo, S.; Fernandez-Luna, A.; Fernandez-Elias, V. E. (Deutsche Zeitschrift für Sportmedizin, 2025)
Problem: Sprinting and jumping are critical in football, demanding explosive power and agility. Effective warm-up protocols are essential for optimizing performance in football players. Whole-body electromyostimulation (WB-EMS) shows promise in boosting neuromuscular activation and post-activation potentiation. This study investigated the effects of WB-EMS-training during the FIFA 11+ warm-up on athletic performance in football. Methods: Ten semi-professional football players (20.42±1.35 years, 72.00±7.98 kg, 177.8±6.8 cm) participated in this crossover study. They performed FIFA11+ warm-ups with and without WB-EMS-training, followed by performance tests including a 20m sprint, long jump, repeated sprint ability (RSA), and match running performance monitored via GPS (Global Positioning System). WB-EMS-training was applied using with 85 Hz frequency, 350 µs pulse width, and 6-second intermittent stimulation periods. Statistical analysis included ANOVA and paired t-tests. Results: WB-EMS-training did not significantly improve sprint times (p=0.17), long jump (p=0.25), RSA (p>0.05), or match running performance (p=0.09) compared to the control. Effect sizes ranged from 0.02 to 1.08. Discussion: WB-EMS-training during FIFA11+ warm-up does not improve athletic performance. While WB-EMS-training shows potential for enhancing neuromuscular activation, our findings suggest limited effects. Potential reasons include insufficient intensity, lack of individualization, and match dynamics overshadowing warm-up effects. Additional research is needed to determine the optimal parameters of WB-EMS-training. Conclusion: WB-EMS-training may not provide additional advantages during warm-ups for young football players. Future studies should explore protocol optimization and larger cohorts.